2010
DOI: 10.1007/s10140-010-0864-0
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava dissection following blunt abdominal trauma

Abstract: Dissection of the inferior vena cava (IVC) is rare, with only a few published reports in the literature. It is usually associated with blunt abdominal injury or iatrogenic injury from a catheter manipulation. Venous dissections are rare due to lack of well-developed layers in the walls (intima, media and adventitia), low pressure in the venous system, and the absence of atherosclerotic changes. However, IVC dissection is associated with a high mortality rate due to the difficulty in diagnosis, technically diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Inferior vena cava (IVC) injuries lead to high rates of morbidity and mortality. Studies reported that more than one-third of patients with an IVC injury has a mortality rate of more than 60 % after admission to hospital (14,15). Accordingly, hemodynamic status and prompt identi cation of bleeding source are in focus when treating patients suffering from abdominal vascular injuries (16).…”
Section: Discussionmentioning
confidence: 99%
“…Inferior vena cava (IVC) injuries lead to high rates of morbidity and mortality. Studies reported that more than one-third of patients with an IVC injury has a mortality rate of more than 60 % after admission to hospital (14,15). Accordingly, hemodynamic status and prompt identi cation of bleeding source are in focus when treating patients suffering from abdominal vascular injuries (16).…”
Section: Discussionmentioning
confidence: 99%
“…Inferior vena cava (IVC) injuries lead to high rates of morbidity and mortality. Studies reported that more than one-third of patients with an IVC injury has a mortality rate of more than 60% after admission to hospital 19 , 20 . Accordingly, hemodynamic status and prompt identification of bleeding source are in focus when treating patients suffering from abdominal vascular injuries 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of known post-traumatic IVC thrombosis, there are two reports of IVC filter placement via the right internal jugular approach, including a suprarenal filter that was retrieved after 8 weeks. 9 , 10 Suprarenal IVC filters have also been placed without significant complications in patients with recurrent pulmonary embolism due to non-traumatic IVC thrombosis extending to or above the renal veins and in patients with renal or gonadal vein thrombosis. 11 Recent advances in filter designs and increasing experience in filter retrieval make suprarenal IVC filters a feasible choice in the correct clinical settings.…”
Section: Discussionmentioning
confidence: 99%